PENGEMBANGAN PELAKU USAHA MELALUI PELATIHAN MANAJEMEN USAHA DAN PENYUSUNAN LAPORAN KEUANGAN - Wahyu Maulana; Nurul Alfian (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2021)
Every business actor has problems with different levels of difficulty because the human resources in them come from different educational backgrounds and experiences. Problems with business management and non-standard preparation of financial reports are things that must be addressed in order to make a business more organized. This is felt by several business actors in Kaduara Barat village, Pamekasan Regency, where the majority of them run their businesses without paying attention to organized business management and proper financial reports. The results of this service are as follows: 1. The layout of the products sold in stores is more organized so that consumers feel comfortable shopping; 2. The division of tasks must be clear so that there are no overlapping jobs / positions with multiple positions; 3. In terms of service and marketing, business actors realize the need for a